CD4 T-Cell Responses in Primary HIV Infection: Interrelationship with Immune Activation and Virus Burden - Chevalier, Mathieu F. (Front Immunol, 2016)
Early events during primary HIV infection (PHI) are thought to influence disease outcome. Although a growing body of evidence suggests a beneficial role of HIV-specific CD4 help in HIV infection, it is unclear how early viral replication, systemic immune activation, and antiretroviral therapy (ART) may shape CD4 T-cell responses during PHI, and whether HIV-specific CD4 responses contribute to the high immune activation observed in PHI. Twenty-seven patients with early PHI were included in a prospective longitudinal study and 12 of them received ART after enrollment. Fresh peripheral blood mononuclear cells were used for measurement of ex vivo T-cell activation and of cytokine-producing CD4 T-cells following stimulation with PMA/ionomycin or HIV-1-gag-p24 antigen. Patients were segregated based on CD8 T-cell activation level (i.e., % HLA-DR(+)CD38(+) CD8 T-cells) at baseline (BL). Patients with lower immune activation exhibited higher frequency of bulk CD4 T-cells producing IFN-γ or IL-17 and higher effector-to-regulatory cell ratios. No differences were found in HIV-specific CD4 T-cell frequencies. In contrast, segregation of patients based on plasma viral load (pVL) revealed that patients with higher pVL showed higher cytokine-producing HIV-specific CD4 responses. Of note, the frequency of IFN-γ(+) HIV-specific CD4 T cells significantly diminished between BL and month 6 only in ART-treated patients. However, early treatment initiation was associated with better maintenance of HIV-specific IFN-γ(+) CD4 T-cells. These data suggest that HIV-specific CD4 responses do not fuel systemic T-cell activation and are driven by viral replication but not able to contribute to its control in the early phase of infection. Moreover, our data also suggest a benefit of early treatment for the maintenance of HIV-specific CD4 T-cell help.